PENEREPAN MODEL PEMBELAJARAN PROBLEM POSING DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SMP SWASTA CITRA SAKTI MANIAMOLO - Trifosa Fau (Universitas Nias Raya, 2023)
The problem of this research is the lack of improvement in student learning outcomes. The aim of this research is To determine the application of the problem posing learning model in improving student learning outcomes in the Pancasila and Citizenship Education subject in class VIII of Citra Sakti Maniamolo Private Middle School for the 2023/2024 academic year. So the conclusion is that through the application of this problem posing learning model it can increase student creativity in learning Pancasila and Citizenship Education in class VIII of Citra Sakti Private Middle School. This can be seen from the increase in student learning outcomes and the assessment of creativity test results for each cycle, which consists of cycle I (first) and cycle II (second). Suggestions from researchers In order to emphasize making questions, students or students should be able to get used to working together with other students in group discussions, being active and in learning activities such as asking questions and being able to express opinions so that they will increase information and knowledge. It should be able to provide teachers with experience in using the problem posing learning model with an emphasis on problem solving, critical thinking, and involving students in solving problems.